Privacy and Team Incentives - BUFFA, ANDREA M.; LIU, QING; WHITE, LUCY (Journal of Finance, 2025)
ABSTRACT Real‐world contracts are typically private, observed only by their direct signatories, so agents working together are vulnerable to the principal opportunistically reducing other agents' incentives. The principal can mitigate this commitment problem by giving the most skilled agent a budget and delegating authority to write other agents' contracts. This endogenous hierarchy, never optimal with public contracts, raises effort, output, and compensation but allows rent extraction. The principal prefers it when contracts are opaque enough, skill is sufficiently heterogeneous across agents, and joint output is sensitive enough to effort. Our model provides novel predictions for the structure of banking syndicates.